ISE-ammonium sensors in WRRFs: field assessment of their influencing factors. Issue 4 (26th February 2019) - Cecconi, Francesca; Reifsnyder, Samuel; Ito, Yuichi; Jimenez, Margil; Sobhani, Reza; Rosso, Diego
Abstract : Real-time quantification of the ammonium content in water resource recovery facilities (WRRFs) has received attention in recent years for both monitoring and process control. Abstract : Real-time quantification of the ammonium content in water resource recovery facilities (WRRFs) has received attention in recent years for both monitoring and process control. Ion-selective electrodes are a viable solution for online ammonium measurements with an increasing number of installations worldwide. This paper describes a year-long field evaluation of ISE-ammonium sensors and discusses the sensor performance under different operating conditions during diurnal and seasonal variations. Three ISE-ammonium sensors were installed in the aeration tank of an activated sludge process. Specifically, one probe was installed at the end of the aeration tank, to test the sensor under low range conditions (<1 mg N-NH4 + per L). Several factors influencing the sensor in field applications are presented critically, such as fouling, interfering ions, disturbance from aeration bubbles, and various maintenance and operating procedures. This study highlights how the background ion content of the mixed liquor affects the performance of the low range application. We recorded a 40% error in the N-NH4 + concentration over the low range measurement (<1.0 mg L −1 ) due to the K + and Na + content (18 and 225 mg L −1 on average, respectively). This 40% error exceeds the sensor precision by 1 log. Therefore, for low range installation, the background interference due to other cations represents the main bottleneck in the current state of this technology. On the other hand, for the high range application, the ion interference led to an error comparable in magnitude to a sensor precision of 5%. Sensor fouling was tracked over time during operation: both reversible fouling and irreversible fouling were observed, and it differed according to the application and therefore, to the wastewater composition. Different operation and maintenance procedures were addressed, and this study points out how overzealous maintenance or an improper procedure can be counterproductive.